Bridging With Extracorporeal Membrane Oxygenation Under the New Heart Allocation System: A United Network for Organ Sharing Database Analysis. (May 2021) - Nordan, Taylor; Critsinelis, Andre C.; Mahrokhian, Shant H.; Kapur, Navin K.; Thayer, Katherine L.; Chen, Frederick Y.; Couper, Gregory S.; Kawabori, Masashi
Abstract : Background: The effect of the new donor heart allocation system on survival following bridging to transplantation with venous-arterial extracorporeal membrane oxygenation remains unknown. The new allocation system places extracorporeal membrane oxygenation–supported candidates at the highest status. Methods: The United Network for Organ Sharing database was queried for adults bridged to single-organ heart transplantation with extracorporeal membrane oxygenation from October 2006 to February 2020. Association between implementation of the new system and recipient survival was analyzed using Kaplan-Meier estimates, Cox proportional hazards models, and propensity score matching. Results: Of 364 recipients included, 173 and 191 were transplanted under new and old systems, respectively. Compared with the old system, waitlist time was halved under the new system (5 versus 10 days, P <0.01); recipients also demonstrated lower rates of prior cardiac surgery (32.9% versus 44.5%, P =0.03) and preoperative ventilation (30.6% versus 42.4%, P =0.02). Unadjusted 180-day survival was 90.2% (95% CI, 84.7%–94.2%) and 69.6% (95% CI, 62.6%–76.1%) under the new and old systems, respectively. Cox proportional hazards analysis demonstrated listing and transplantation under the new system to be an independent predictor of post-transplant survival (adjusted hazard ratio, 0.34 [95% CI 0.20–0.59]). Propensity score matching demonstrated a similar trend (hazard ratio, 0.36 [95% CI, 0.19–0.66]). Candidates listed under the new system were significantly less likely to experience waitlist mortality or deterioration (subhazard ratio, 0.38 [95% CI, 0.25–0.58]) and more likely to survive to transplant (subhazard ratio, 4.29 [95% CI, 3.32–5.54]). Conclusions: Recipients transplanted following extracorporeal membrane oxygenation bridging to transplantation under the new system achieve greater 180-day survival compared with the old and demonstrate less preoperative comorbidity. Waitlist outcomes have also improved significantly under the new allocation system. Abstract : Supplemental Digital Content is available in the text.